Les transcrits bcr-abl et leurs corrélations avec l’hémogramme au cours de la leucémie myéloïde chronique (LMC) au Togo - Padaro, Essohana (Pan Afr Med J, 2018)
This study aims to describe the different bcr-abl gene transcript variants in order to determine their frequency and to study their influence on CBC diagnostic test. We conducted a cross-sectional study of 34 patients with chronic myeloid leukemia in Togo. The search for fusion transcripts was performed in the laboratory of biological haematology at the Henri Mondor Hospital, Créteil (France). The average age of patients was 42,32±14,87 years ranging between 9 and 65 years. Most patients were male, with a sex- ratio of 1.61 (21 men and 13 women). Molecular examination showed b3-a2 transcript and b2-a2 transcript. Nineteen patients (55.88%) expressed b3-a2 transcript, 13 patients (38.24%) b2-a2 transcript (32.10%) and two patients expressed both b3-a2 and b2-a2 transcripts (5.88%). At diagnosis, mean hemoglobin level, the average number of white blood cells and the average number of platelets in patients expressing b3-a2 transcript were 99,2g/L; 207,63g/l and 451,28g/l respectively. In patients expressing b2-a2 transcript values were 104,6g/l, 114,32g/l and 486,11g/l. In patients with both transcripts, values were 67g/L, 867g/l and 780g/l respectively. CBC parameters are more significantly altered in patients with both transcripts b3-a2 and b2-a2.